2001
DOI: 10.4049/jimmunol.166.7.4341
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Soluble CD100. I. The Extracellular Region of CD100 Is Released from the Surface of T Lymphocytes by Regulated Proteolysis

Abstract: CD100 is the first semaphorin described in lymphoid tissues, where it has been shown to be associated with a serine kinase activity. Semaphorins are molecules involved in axon pathfinding during nerve development and act as repellent guidance cues. In the nervous system semaphorins exist as either membrane-bound or secreted forms. We report here a spontaneous processing of membrane CD100, suggesting that it is also produced as a diffusable semaphorin from lymphoid cells. Monomeric and homodimeric forms of CD10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 49 publications
6
124
0
4
Order By: Relevance
“…In some respects, the recruitment and subsequent shedding of sema4D as a bioactive fragment resemble the behavior of CD40L, which is also shed from the surface of activated platelets (32). An earlier study showed that sema4D cleavage in Jurkat cells is inhibited by EDTA and EGTA but failed to detect inhibition by the metalloprotease inhibitor, GM6001 (17). The present studies show that in platelets cleavage is blocked by GM6001 or TAPI-2, and both pharmacologic and genetic evidence points toward ADAM17, either serving as the sema4D sheddase or providing a necessary step before the actual sheddase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some respects, the recruitment and subsequent shedding of sema4D as a bioactive fragment resemble the behavior of CD40L, which is also shed from the surface of activated platelets (32). An earlier study showed that sema4D cleavage in Jurkat cells is inhibited by EDTA and EGTA but failed to detect inhibition by the metalloprotease inhibitor, GM6001 (17). The present studies show that in platelets cleavage is blocked by GM6001 or TAPI-2, and both pharmacologic and genetic evidence points toward ADAM17, either serving as the sema4D sheddase or providing a necessary step before the actual sheddase.…”
Section: Discussionmentioning
confidence: 99%
“…Although cleavage of sema4D has been observed in T cells (17,18), the protease responsible has not been identified. The observation that sema4D cleavage can occur in washed platelets implies that the protease involved is intrinsic to the platelets and not a plasma protein.…”
Section: Sema4d Is An Integral Protein With a Large N-terminal ␤-Propmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, certain membrane-bound semaphorins (e.g., Sema4D) are proteolytically released ("shed") in the extracellular space in active form. 14,15 Available data indicate that the control of cell migration by semaphorin signals follows three paradigms, illustrated in Figure 1: (A) membrane-bound semaphorins at the cell surface can mediate localized signals to guide migration; (B) secreted/shed molecules can diffuse in the area of expressing cells, and demarcate it as a "no entry" zone (or instead form a chemotactic gradient) for cell populations expressing the specific receptors; (C) migrating cells may establish autocrine loops of secreted/shed semaphorins, to police their own migration: e.g., it was found that the inactivation of autocrine Sema3A signaling in endothelial cells results in increased directional persistence. 16 What are the molecular pathways underlying the control of cell adhesion and cell migration by semaphorins?…”
Section: Functional Role Of Semaphorins In Cell Adhesion and Cell Migmentioning
confidence: 99%
“…Foi inicialmente identificada em linfócitos T ativados (BOUGERET et al, 1992) e posteriormente em outros tipos celulares, tanto humanos quanto murinos. CD100 pode ser encontrada como uma proteína de 150 kDa ligada à membrana ou como uma molécula solúvel de 120 kDa (sCD100), originada por uma clivagem proteolítica (ELHABAZI et al, 2001, BASILE et al, 2007, ZHU et al, 2007.…”
Section: Cd100 Seus Receptores E O Sistema Imuneunclassified